Concentration dependence of hydrogen diffusion in clamped vanadium (0 0 1) films. (24th November 2016) - Huang, Wen; Mooij, Lennard P A; Droulias, Sotirios A; Palonen, Heikki; Hartmann, Ola; Pálsson, Gunnar K; Wolff, Max; Hjörvarsson, Björgvin
Abstract: The chemical diffusion coefficient of hydrogen in a 50 nm thin film of vanadium (0 0 1) is measured as a function of concentration and temperature, well above the known phase boundaries. Arrhenius analysis of the tracer diffusion constants reveal large changes in the activation energy with concentration: from 0.10 at 0.05 in H V −1 to 0.5 eV at 0.2 in H V −1 . The results are consistent with a change from tetrahedral to octahedral site occupancy, in that concentration range. The change in site occupancy is argued to be caused by the uniaxial expansion of the film originating from the combined hydrogen induced expansion and the clamping of the film to the substrate.